Analytical Study of Nonlinear Vibrations of the Tympanic Membrane by Homotopy Perturbation Method - Rahmani , Masoud; Moslemi Petrudi, Amin; Cristian Scurtu , Ionut (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Nonlinear vibration problems are generally of great importance in physics, mechanical structures, and other engineering research. This type of equation is very difficult and time-consuming. Researchers, therefore, focus on analytical and numerical methods; In this paper, using the new Newton-Harmonic Balance analytical method, which includes a combination of Newton methods and the harmonic balance method, the common Homotopy Perturbation method is used to solve the nonlinear equation of human tympanic membrane vibration and are compared and validated.